الاتساق المعجمي في سورة القصص دراسة لسانية نصية - حمدان, سليم; كرباع,جبارية; فارح, نور الاسلام (University of Eloued جامعة الوادي, 2024)
يسعى الاتساق المعجمي إلى الربط بين عناصر النص، فهو وحدة لغوية ومظهر من مظاهر السبك، ومن خلال هذه الدراسة نقدم ملخص يشمل ما قيل سابقا حول موضوع البحث: - يمتاز الاتساق المعجمي بظاهرتين التكرار والتضام، فهما يعتبران ظاهرة لغوية - يسهم رصد التكرار داخل النص في معرفة مفاتيحه فهو يسهل على القارئ فهم النص - بينما يسهم التضام في تسلسل اكلام فهو يحقق الوظيفة الاستمرارية لمعاني النص، مما يساعد في اتساقه. - قد خلّف كلا التكرار والتضام قيمة فنية جمالية داخل النص، ويشكل كلاهما ايقاعا في الكلام، اذن لهما ميزة صوتية معنوية اسلوبية والغاية في التأثير في نفس المتلقي Lexical cohesion aims to link elements of the text, serving as a linguistic unit and a manifestation of cohesion. Through this study, we present a summary encompassing previous discussions on the research topic: - Lexical cohesion is characterized by two phenomena: repetition and collocation, both of which are considered linguistic phenomena. - Tracking repetition within the text helps identify its keys, making it easier for the reader to understand the text. - Collocation contributes to the sequence of speech, achieving the continuity of the text's meanings, thereby aiding in its cohesion. - Both repetition and collocation have left an artistic and aesthetic value within the text, creating a rhythm in speech. Thus, they possess phonetic, semantic, and stylistic features aimed at influencing the receiver's perception.
لسانيات عامة
Keywords: لسانيات النص، الاتساق المعجمي، التكرار، التضام; Text linguistics; lexical cohesion; repetition; collocation